Nikah Mut’ah Sebagai Alternatif Hukum Perkawinan Islam: Telaah Terhadap Pemikiran Sudirman Tebba - Khusniati Rofi'ah (Faculty of Sharia UIN Kiai Ageng Muhammad Besari Ponorogo, 2012)
Islamic law as a social ”˜institution’ is substantively to control society and to response amount of problems which human does. Mujtahids as Islamic creative thinkers should have standard competence to reformulate and to anticipate problems appear at their community. Sudirman Tebba, who often studies many problems such as zina (”˜illegal sexual relations), is one of Islamic law creative tinkers in Indonesia. According to him, illegal sexual relations do not impact of liberal culture merely. It can be effect of both bureaucracy system and legal law officers. Tebba recommends nikah mut’ah as a solution to this problem. Nikah mut’ah, which muslim community does at early Islam, is a procedur to legalize nikah. Theoretically, nikah mut’ah is contrary to functional structural as Talcot Person theorizes. Person states that family structure, individually, has a function and position. There is a limitation of time for Nikah mut’ah. So a husband will not be at his functional position. Tebba statement, will probably ease people to legalize their marriage, but it at the other hand will affect bigger negative problems. It is a contra productive to Islamic law, which takes care of and protects humanities. This short article is to show how functional structural theory sees nikah mut’ah as Islamic law works, and what does it implication to society in Indonesia.